Controlling mechanical undesirable side effects with a tooth indicated for extraction: free anchorage - Monini, André da Costa; Gandini Júnior, Luiz Gonzaga [UNESP]; Gandini, Márcia Regina Elisa Aparecida Schiavon; Leite, Gustavo Maiola de Souza; Vianna, Alexandre Protásio (Quintessence Publishing, 2013)
This manuscript describes the use of a tooth indicated for extraction due to orthodontic reasons as an anchorage aid to receive undesirable side effects caused by orthodontic uprighting of a contralateral molar tooth. The mandibular right second molar was mesially tipped as a result of loss of the adjacent first molar. Since the treatment plan involved extraction of the mandibular left first premolar, undesirable side effects associated with the molar uprighting movement were transferred to this tooth. Once the second molar was vertical, the premolar was extracted and the treatment continued. The results suggest that treatment time can be reduced if undesirable orthodontic mechanical side effects can be directed to a tooth whose extraction is indicated.
Keywords: Orthodontic anchorage procedures; Tooth movement